Work-related Sense of Coherence Scale: Reliability and validity of scores in a South African sample. Issue 3 (30th June 2016) - van der Westhuizen, Sanet; Ramasodi, Elsie
Abstract : The study investigated the reliability and validity of scores from the Work-related Sense of Coherence Scale (Work-SoC) in a South African sample. Respondents were 326 employees from the retail industry sector in Gauteng province of South Africa (females = 48%, blacks = 38%, married = 42%, English = 40%). They completed the Work-SoC questionnaire, and the Utrecht Work Engagement Scale (UWES). Confirmatory factor analysis, Cronbach alpha coefficients, correlations and descriptive statistics were utilised to analyse the data. The results indicated a correlated three-factor structure of Work-SoC consisting of comprehensibility (four items), manageability (two items) and meaningfulness (three items). A three-factor structure fitted the data better than a one-factor structure. Work-SoC was practically significantly related to work engagement. All three sub-scales and the total scale of the Work-SoC Questionnaire displayed acceptable internal consistencies above the required 0.70. The Work-SoC Scale appears to yield scores usable with South African employees.